A Case of Resistance to Thyroid Hormone with Chronic Thyroiditis: Discovery of a Novel Mutation (I54V). (9th October 2011) - Kammoun, I.; Bouzid, C.; Kandara, H.; Ben Salem, L.; Turki, Z.; Ben Slama, C.
Abstract : Resistance to thyroid hormone (RTH) is a rare disorder characterized by variable tissue hyporesponsiveness to thyroid hormone, usually caused by mutations in the thyroid hormone receptor beta (TR β ). It has been reported that the serum of patients with RTH is free of auto-antibodies against thyroglobulin (Tg) and thyroid peroxidase (TPO), except in rare cases where coincidental autoimmune thyroiditis is also present. We describe a 13-year-old girl with chronic thyroiditis and RTH. This patient had increased plasma free T3, free T4 at the upper limits with unsuppressed TSH. She had peripheral manifestations of thyroid hormone excess, hypertension and growth acceleration. Anti-TPO antibodies were positive. Sequence analysis of the TR β gene was performed and revealed a novel mutation I54V in exon 4. The same mutation was also found in the mother and two asymptomatic sisters. The clinical presentation of our patient is not habitual in RTH because growth retardation is frequently reported in this syndrome. The association between RTH and thyroiditis complicate the management of the hypothyroidism.